Iberia-Forams cruise in September 2012 - coccolithophore assemblage data - Voelker, Antje H L (PANGAEA, 2025)
These data present results from seawater samples collected at 11 stations in a north-south transect along the western and southwestern Iberian margin in September 2012. Seawater samples at defined depths across the upper 300 meters were filtered in order to perform qualitative and quantitative analysis of extant coccolithophores. For species identification a piece of the filter paper was cut off and analyzed in a Scanning Electronic Microscope at the University of Salamanca (Spain). The aim of this work was studying the composition of the coccolithophore assemblages along the western Iberian margin as well as across the water column at each station. Approximately 15 species were identified. Two vertical zones, separated by a seasonal or a permanent thermocline, can be distinguished in the photic zone: the upper part, counting on more diversity and dominated by small placoliths; and the lower part, mainly inhabited by Florisphaera profunda. Minor changes are encountered with regard to the horizontal distribution, where temperature is likely the dominant environmental variable.
Keywords: Coccolithophores; CTD data; Iberian margin